Rewriting the Sacred: Mythopoesis and Cultural Identity in Contemporary Indonesian Novels - Ria Kasanova; Mohammad Rudiyanto (Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyse the processes of mythopoesis in the contemporary Indonesian novels Tanah Tabu by Anindita S. Thayf, Burung-Burung Manyar by Y.B. Mangunwijaya, and Para Priyayi by Umar Kayam in reconstructing myths and articulating plural and dynamic cultural identities. The methodology used was a qualitative analysis with a literary discourse approach that emphasised contextual and critical interpretations of the text. The main focus of this research is the patterns of mythopoesis, the narrative function of myths, and the articulation of cultural identity as a result of negotiations between tradition and modernity, local and national, and subaltern and hegemonic. The findings reveal that mythopoesis in the three novels serves as a creative and critical mechanism to affirm and revitalise cultural heritage, while also functioning as a tool for legitimising social-political struggles and criticising modernity and hegemonic state power practices. The cultural identity produced through the process of rewriting myths is not essentialist but plural and constantly evolving in response to dynamic socio-political contexts. These findings reinforce Hall's theory of cultural identity and Homi Bhabha's concept of hybridity, regarding identity as a continuously negotiated construction. The contribution of this research lies in the development of contemporary Indonesian literary studies through an understanding of mythopoesis as a narrative strategy that plays a role in identity formation and social criticism. The practical implications of this research are also relevant for literary education because it prioritises critical and contextual approaches to understanding Indonesia's cultural diversity.